2014
DOI: 10.1016/j.ultsonch.2013.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between conventional, ultrasound-assisted and microwave-assisted methods for extraction of anthraquinones from Heterophyllaea pustulata Hook f. (Rubiaceae)

Abstract: This work reports a comparative study about extraction methods used to obtain anthraquinones (AQs) from stems and leaves of Heterophyllae pustulata Hook (Rubiáceae). One of the conventional procedures used to extract these metabolites from a vegetable matrix is by successive Soxhlet extractions with solvents of increasing polarity: starting with hexane to eliminate chlorophylls and fatty components, following by benzene and finally ethyl acetate. However, this technique shows a low extraction yield of total AQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 28 publications
1
21
0
2
Order By: Relevance
“…It is important to note that PHWE extractions showed an AQs recovery enhancement of up to 600% compared with traditional Soxhlet process with solvents of increasing polarity. As it was demonstrated in previous work [22], only a AQs yield of about 3-4 mg total AQs/g vegetable matrix was obtained using Soxhlet extraction for 16 h. On the other hand, using PHWE the extraction time is reduced from 16 h to 2 h. This high yield of AQ obtained by PHWE, is mainly due to the ability of the water to reduce the dielectric constant with increasing temperature, by modifying its polarity is possible to extract non-polar organic compounds. Furthermore, the temperature used in the high pressure process is higher than in Soxhlet extraction, favoring the extraction of solid compounds as AQs.…”
Section: Effect Of Water Flow Rate On the Extractionsupporting
confidence: 73%
See 1 more Smart Citation
“…It is important to note that PHWE extractions showed an AQs recovery enhancement of up to 600% compared with traditional Soxhlet process with solvents of increasing polarity. As it was demonstrated in previous work [22], only a AQs yield of about 3-4 mg total AQs/g vegetable matrix was obtained using Soxhlet extraction for 16 h. On the other hand, using PHWE the extraction time is reduced from 16 h to 2 h. This high yield of AQ obtained by PHWE, is mainly due to the ability of the water to reduce the dielectric constant with increasing temperature, by modifying its polarity is possible to extract non-polar organic compounds. Furthermore, the temperature used in the high pressure process is higher than in Soxhlet extraction, favoring the extraction of solid compounds as AQs.…”
Section: Effect Of Water Flow Rate On the Extractionsupporting
confidence: 73%
“…The plant material was air-dried at room temperature during seven days and separated into stems and leaves. Based on previous works [22] only stems were used for the study presented in this manuscript because of the AQs content in the stems is higher than the other plant parts.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Vázquez et al [56] reported that the UAE provided an extraction yield of 168 mg/g dry weight (DW) in the recovery of anthraquinones from stems of Rubiáceae, exceeding the extraction yield obtained by the Soxhlet method (34 Mg/g DW). In addition, there was a reduction on the extraction time of 16 to 2 h; a reduction in the amount of solvent used (from 36 mL/g to 20 mL/g) was also observed.…”
Section: Comparison Against Conventional Methodsmentioning
confidence: 99%
“…Also, it is important to note that the AQs yield extraction obtained is similar to yield obtained by traditional extraction methods for AQs, wich involve the use of a Soxhlet apparatus with organic solvents of increasing polarity, starting with hexane, followed by benzene, ethyl acetate, and ethanol (Barrera Vázquez et al, 2014). However, the UAE using ethanol presents Table 5 Comparison of extraction methods analyzed.…”
Section: Comparison Of Uae With Conventional Soxhlet Extractionsmentioning
confidence: 70%
“…Ethanol is a non-toxic and economic solvent widely used in the extraction of active principles from plants (Barrera Vázquez et al, 2014). Being a polar organic solvent, ethanol is in principle an adequate solvent for the slightly polar AQs molecules.…”
Section: Introductionmentioning
confidence: 99%